Development of Adaptive Learning E-Modules in basic mathematics for slow learners at vocational high schools - Arina, Novra; Bentri, Alwen; Ananda, Azwar; Yeni, Fetri (International Journal of Research in Counseling and Education, 2023)
This study focuses on the development of an E-Module to measure its impact on slow learners at vocational school in Padang, West Sumatra. The research involved 6 slow learner students, utilizing a quantitative approach with a 5-point Likert rating questionnaire. The ASSURE model was employed to analyze the characteristics of each slow learner. The research findings indicate that the practicality level of the E-Module reached 95.87% according to student responses and 96% according to teacher responses, demonstrating the ease of use of the E-Module. Based on the ANOVA test results using Excel, a P-Value of 0.001954 was obtained (p < 0.05), indicating a significant difference in the basic mathematics abilities of the students. This study confirms the validity and reliability of the measurement instrument, indicating that the adaptive learning E-Module has a positive impact on supporting the learning of slow learners.